Nicole Brossard : Selections - Brossard, Nicole (Book collections on Project MUSE., 2010)
"Pleasure," Jennifer Moxley writes in her introduction to this volume, "is the word that first comes to mind at the mention of Nicole Brossard's poetry." This volume provides English-language readers with an overview of the life and work of Nicole Brossard, poet, novelist, and essayist, who is widely recognized in her native Quebec and throughout the French-speaking world as one of the greatest writers of her generation. Brossard's poetry is rooted in her investigations of language, her abiding commitment to a feminist consciousness, and her capacity for renewing meaning as a virtual space of